The Meaning of Procotan Porry in the Tradition of Pregnancy in the Sacral and Prophant Perspective - khuzaimah Khuzaimah; Arif Sudrajat (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
Food in Indonesian society has certain symbols to convey. one of which is the presentation of procotan porridge which is expected to be able to make the baby's birth run smoothly. The existence of this phenomenon makes researchers want to know the meaning of procotan porridge in the tradition of pregnancy in Javanese society using a cultural sociology perspective. The purpose of this study is to find out the meaning contained in the tradition of serving the porridge. This study uses a qualitative method. the data were obtained from interviews with the Javanese community in KAras Village, Central Java and also from literature studies. Then the data were analyzed using the analysis of the sacred theory of Emil Durkheim. The results of the study show that procotan porridge has sacred and profane meanings. This sacred meaning can be seen from the manufacture, which must match the mother's weton and must also be present during the first pregnancy. However, this procotan porridge is also a profane thing as porridge or ordinary food and may be violated or not made during the second, third, and so on pregnancies. Keywords: procotan-sacred-profane-Emile Durkheim-tradition